2015
DOI: 10.4187/respcare.03699
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Factors Associated With Respiratory Care Protocol Use

Abstract: BACKGROUND: Organizational factors associated with adoption and use of respiratory care protocols have received little attention. This study examines patterns of protocol use and features of a hospital and providers that are associated with respiratory care protocol use. METHODS: Forty-four hospitals and their health-care providers responded to an online survey regarding perceived outcomes of protocol use and their level of support for using protocols. Hospital features (ie, size, teaching status, and use of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…This reinforces previous research on these phenomena. As Metcalf et al 6 report, greater use of protocols increases RT job satisfaction. Although the survey did not directly ask about job satisfaction, it can be surmised that increasing the status and value of RTs could lead to enhanced job satisfaction.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This reinforces previous research on these phenomena. As Metcalf et al 6 report, greater use of protocols increases RT job satisfaction. Although the survey did not directly ask about job satisfaction, it can be surmised that increasing the status and value of RTs could lead to enhanced job satisfaction.…”
Section: Discussionmentioning
confidence: 89%
“…Protocols have been reported to decrease unnecessary or harmful therapy, healthcare costs, and hospital length of stay while improving resource utilization, effectiveness and appropriateness of care, consistency of care, and patient outcomes, thereby improving the overall quality of patient care. [2][3][4][5][6][7][8] Protocols involving numerous interventions, including oxygen titration, therapeutic interventions, and ventilator weaning, have been described and reported in the literature. [9][10][11][12][13] These studies range from retrospective reviews to randomized controlled trials.…”
Section: Introductionmentioning
confidence: 99%
“…The recruitment of hospitals and participating RTs and managers and the deployment of the online surveys were as described previously. 5 In brief, collected data elements included RTs' perceptions of job satisfaction, turnover intentions, and job stress. Managers were queried regarding the level of protocol use within each participating hospital unit.…”
Section: Samplementioning
confidence: 99%
“…Because employees' perceptions and experiences in their jobs have been shown to affect productivity and performance, 4 respiratory care managers must consider how work design impacts RT job satisfaction and turnover intentions. A previously reported multi-hospital, survey-based report regarding determinants of respiratory care protocol use 5 provides the basis for this more detailed analysis of the impact of respiratory care protocol use on RT job satisfaction and turnover intentions. Specifically, we examine the effect of respiratory care protocol use on RT overall job satisfaction, turnover intentions, and perceived job stress.…”
Section: Introductionmentioning
confidence: 99%
“…The authors identify that physician support is a characteristic found in centers that use protocols, as is use of high-quality information systems. The work by Metcalf et al 14 falls short in providing the reader with information on why protocols fail to be widely adopted. Although further investigation may yield such detail, the respiratory care community has a new incentive to consider the use of protocols.…”
mentioning
confidence: 99%